1999
DOI: 10.1093/oxfordjournals.epirev.a017992
|View full text |Cite
|
Sign up to set email alerts
|

Improving Immunization Coverage Rates: An Evidence-based Review of the Literature

Abstract: This systematic review evaluates the effectiveness of population-based interventions to improve vaccination coverage. The paper 1) presents a framework for evaluating interventions to improve vaccination coverage, 2) describes selected strategies for improving coverage, and 3) systematically reviews available information on the effectiveness of these strategies in improving vaccination coverage and other outcomes to assess their effectiveness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
109
0
4

Year Published

2001
2001
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(114 citation statements)
references
References 160 publications
(267 reference statements)
1
109
0
4
Order By: Relevance
“…These include the use of reminder and recall strategies, assessment of vaccination coverage at the provider or clinic level and feedback of information to the provider, and parent and provider education conducted as part of multi-component interventions. 21,26 Numerous studies have documented the effectiveness of these strategies in raising vaccination coverage among children in various settings, including children in urban and inner-city areas. 21,26 For example, a recent review of the effectiveness of parent reminder and recall systems found that children exposed to reminders were twice as likely to be UTD with immunizations as children not exposed to such strategies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These include the use of reminder and recall strategies, assessment of vaccination coverage at the provider or clinic level and feedback of information to the provider, and parent and provider education conducted as part of multi-component interventions. 21,26 Numerous studies have documented the effectiveness of these strategies in raising vaccination coverage among children in various settings, including children in urban and inner-city areas. 21,26 For example, a recent review of the effectiveness of parent reminder and recall systems found that children exposed to reminders were twice as likely to be UTD with immunizations as children not exposed to such strategies.…”
Section: Discussionmentioning
confidence: 99%
“…21,26 Numerous studies have documented the effectiveness of these strategies in raising vaccination coverage among children in various settings, including children in urban and inner-city areas. 21,26 For example, a recent review of the effectiveness of parent reminder and recall systems found that children exposed to reminders were twice as likely to be UTD with immunizations as children not exposed to such strategies. 21 By improving office practice for assessing children's immunization status during clinical encounters and administering indicated vaccines, reminder and recall systems as well as provider feedback strategies can potentially reduce missed opportunities.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 Approximately 1 in 4 children aged 19 to 35 months has missed at least 1 recommended vaccine. 2 Reminder and recall messages sent by mail or telephone have been found effective at increasing childhood immunization coverage rates in many settings, 4,5 including private practices, 4 academic centers, 6,7 health maintenance organizations, 8,9 and public health clinics. 10 -13 On the basis of this evidence, the Task Force on Community Preventive Services in 1999 strongly recommended that all practices implement these approaches.…”
Section: Espite Increases In Immunization Coveragementioning
confidence: 99%
“…15 In 1999, the Task Force on Community Preventive Services reviewed studies on the effectiveness of schoolentry laws and found 6 regional studies of school-entry laws for young children that were associated with reductions in disease rates and outbreaks and 3 national studies that showed that states with school-entry laws had lower incidence rates for mumps and measles than states without such laws. 7,8 These effects were particularly strong where the laws were enforced by excluding unvaccinated, nonexempt children from school. Studies have shown the effectiveness of school-entry laws in hastening the implementation of new recommendations that impact adolescents, as well as vaccine coverage for MMR and Td.…”
Section: Legal and Philosophical Rationales For School-entry Laws In mentioning
confidence: 99%